Sustainable Finance and Small and Medium Enterprises: Germany's Bank-Based Financial System and EU Disclosure Requirements - Jan Greitens (Intereconomics, 2023)
To boost investments into sustainability, small and medium enterprises (SMEs) - a crucial part of the economy - must play a role. The current sustainable finance framework focuses on capital markets. But SMEs normally get external finance from banks, and bank-based financial systems work differently than market-based financial systems. Therefore, the regulation needs to take the characteristics and advantages of bank-financed SMEs into account. Decentralised und individual financing of credible transition plans, rather than extensive disclosure of data, could lead to the necessary rise of investments.
Keywords: G01; G23; G28; 330